Finding Real Owners : Lessons from Estonia's Privatization Program - Nellis, John (World Bank, Washington, DC, 2012)
The Estonian government has quickly privatized more than 90 percent of its industrial and manufacturing enterprises. The Estonian privatization agency batches 30-40 firms and advertises them for sale. The prime goal is to find "real owners" capable of running a durable, productive firm. Purchase offers are judged not only on price, but also on the quality of business plans submitted. In 17 sales, the Estonians have combined strategic investment with voucher exchanges. An unresolved problem is that the face value of the vouchers outstanding far exceeds the likely value of assets being sold. This Note concludes that Estonian privatization has been a success in scope and pace. No private firm has yet failed, and the privatization agency reports that most divested firms are expanding their employment. However, these promising results are tempered by the fact that the 70 privatized firms experiencing problems with installment purchase payments are only being admonished. But this problem, though significant, is not overwhelming.